An investigation on friction hydro-pillar processing. (3rd October 2017) - Vicharapu, Buchibabu; Kanan, Luis Fernando; Clarke, Thomas; De, Amitava
ABSTRACT: Friction hydro pillar processing (FHPP) is a novel technique to fill in crack-holes in thick-walled metal structures by an external stud and forming a solid-state bond between the stud and the metal substrate. During the process, the stud is rotated against the crack-wall to facilitate friction heating and flow of plasticized material for proper filling of the crack-hole. We present here a coupled experimental and numerical study on FHPP of ASTM A36 steel to understand the effect of processing conditions on the joint structure and properties. An axi-symmetric heat transfer analysis is carried out to compute the temperature field. The computed thermal cycles are used to estimate the hardness distribution across the joint. The estimated thermal cycles and hardness distribution are tested with the corresponding experimentally measured results.